Modern solar maximum forced late twentieth century Greenland cooling. Issue 14 (21st July 2015) - Kobashi, T.; Box, J. E.; Vinther, B. M.; Goto‐Azuma, K.; Blunier, T.; White, J. W. C.; Nakaegawa, T.; Andresen, C. S.
Abstract The abrupt Northern Hemispheric warming at the end of the twentieth century has been attributed to an enhanced greenhouse effect. Yet Greenland and surrounding subpolar North Atlantic remained anomalously cold in 1970s to early 1990s. Here we reconstructed robust Greenland temperature records (North Greenland Ice Core Project and Greenland Ice Sheet Project 2) over the past 2100 years using argon and nitrogen isotopes in air trapped within ice cores and show that this cold anomaly was part of a recursive pattern of antiphase Greenland temperature responses to solar variability with a possible multidecadal lag. We hypothesize that high solar activity during the modern solar maximum (approximately 1950s–1980s) resulted in a cooling over Greenland and surrounding subpolar North Atlantic through the slowdown of Atlantic Meridional Overturning Circulation with atmospheric feedback processes.